2007
DOI: 10.1007/s10334-007-0073-3
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of continuous arterial spin labeling perfusion MRI after 7 weeks

Abstract: This study demonstrates the suitability of CASL to consistently detect differences between groups, regions, and resting states even after seven weeks. This emphasizes its usefulness for longitudinal designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
70
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 57 publications
17
70
1
Order By: Relevance
“…Based on the coefficient of variation which was 7.9 % in the global GM ROI, we conclude that the reproducibility of our measurements lies well in the range reported for other pulsed (28)(29)(30) and continuous ASL (31)(32)(33)(34) methods. A recent multi center study at 3T including 28 sites (29) using a PASL method termed QUASAR (35,36) reported values for SD w in GM between 3.01 and 8.12 ml/100 g/min, which suggests that the reproducibility of our measurements is quite high.…”
Section: Discussionsupporting
confidence: 83%
“…Based on the coefficient of variation which was 7.9 % in the global GM ROI, we conclude that the reproducibility of our measurements lies well in the range reported for other pulsed (28)(29)(30) and continuous ASL (31)(32)(33)(34) methods. A recent multi center study at 3T including 28 sites (29) using a PASL method termed QUASAR (35,36) reported values for SD w in GM between 3.01 and 8.12 ml/100 g/min, which suggests that the reproducibility of our measurements is quite high.…”
Section: Discussionsupporting
confidence: 83%
“…CASL, continuous arterial spin labeling; p-CASL, pseudo-continuous arterial spin labeling; s.d., standard deviation; TI PASL, inversion time pulsed arterial spin labeling. on reproducibility of these techniques (Floyd et al, 2003;Gevers et al, 2009a;Hermes et al, 2007;Jahng et al, 2005;Parkes et al, 2004). Looking at mean CBF values and the amount of data dispersion, as indicated by the CVs, we noticed that CASL and single TI PASL data from one site were largely responsible for this discrepancy.…”
Section: Discussionmentioning
confidence: 84%
“…Only one study acquired CBF data both with participants' eyes open and closed. However, the assessment of test-retest reliability of CBF-mean was calculated based on the average CBF-mean of two resting states (Hermes et al, 2007).…”
Section: Test-retest Reliability Of Eyes-open and Eyes-closed Statesmentioning
confidence: 99%
“…BOLD fMRI studies have shown brain activity differences between the EO and EC states in the visual cortex (Jao et al, 2013;Liu et al, 2013;Yang et al, 2007;Zou et al, 2009;Zou et al, 2015), motor and auditory cortices (Jao et al, 2013;Liu et al, 2013;Yuan et al, 2014;Zou et al, 2015), and the default mode network (Jao et al, 2013;Liu et al, 2013;Yan et al, 2009). Using the ASL technique, significant CBF increases in the primary and secondary visual areas (Brodmann area (BA) 17, 18) for EO compared with EC state (Hermes et al, 2007;Zou et al, 2015) have been reported. Thus inconsistencies in resting states across studies may confound comparisons and interpretations among varied studies and impede big-data sharing which is of growing interest.…”
Section: Introductionmentioning
confidence: 99%